Popular Culture and Public Health: A Fresh Approach to Transdisciplinary Public Health Education. (December 2016) - Hudson, Darrell L.
The key to living a longer, healthier life lies in one's ability to maintain a healthy lifestyle and make health behavior changes. Public health professionals face the difficult task of developing effective health communication to encourage healthy lifestyles for an American public distracted by competing demands, such as work obligations and family responsibilities, along with savvy commercial marketing from soft drink makers and fast-food restaurants. Public health educators must do a better job of equipping public health students to meet these challenges. The goal of this article is to describe components of a transdisciplinary problem-solving course, titled "Popular Culture and Public Health, " offered at a private university in the Midwest, geared to help prepare students to meet these challenges. Components from the course described here serves as a model for development of an engaging, solution-oriented course for public health education.